Cell-Free Massive MIMO System With an Adaptive Switching Algorithm Between Cooperative NOMA, Non-Cooperative NOMA, and OMA Modes - Reza Sayyari; Jafar Pourrostam; Mir Javad Musevi Niya (IEEE Access, 2021)
Non-orthogonal multiple access (NOMA) aided cell-free massive multiple-input multiple-output (CF mMIMO) systems have gained great attention over the past few years to be employed in the sixth generation of the wireless network. With distributed antennas over a large area, CF mMIMO systems have much better cell coverage and higher achievable sum-rate compared to the conventional cellular and small-cell networks. This paper will propose a novel cooperative NOMA-aided CF mMIMO system. The proposed scheme will increase the achievable sum-rate and improve the system reliability by creating additional data streams between users within the same NOMA cluster. Also, we will suggest an adaptive switching algorithm between non-cooperative NOMA, cooperative NOMA, and orthogonal multiple access (OMA) modes in order to maximize the power efficiency and achievable sum-rate. We will derive closed-form expressions for the achievable downlink data rates of the mentioned modes. Lastly, we will offer a special user clustering algorithm that needs no complex optimization and ensures the existence of reliable cooperative links between the users. The simulation results will prove the superiority of the proposed scheme over the conventional NOMA-based and OMA-based CF mMIMO systems.